Control of Capsid Transformations during Reovirus Entry - Stephanie L. Gummersheimer; Anthony J. Snyder; Pranav Danthi (Viruses, 2021)
Mammalian orthoreovirus (reovirus), a dsRNA virus with a multilayered capsid, serves as a model system for studying the entry of similar viruses. The outermost layer of this capsid undergoes processing to generate a metastable intermediate. The metastable particle undergoes further remodeling to generate an entry-capable form that delivers the genome-containing inner capsid, or core, into the cytoplasm. In this review, we highlight capsid proteins and the intricacies of their interactions that control the stability of the capsid and consequently impact capsid structural changes that are prerequisites for entry. We also discuss a novel proviral role of host membranes in promoting capsid conformational transitions. Current knowledge gaps in the field that are ripe for future investigation are also outlined.